Sentiment Analysis on Twitter-Based Teleworking in a Post-Pandemic COVID-19 Context - Rojas Rincón, J.S.; Riveros Tarazona, A.R.; Mejía Martínez, A.M.; Acosta-Prado, J.C. (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
The implementation of the telework model has become popular globally due to the COVID-19 pandemic. However, this new model of work organization generates conflicting opinions regarding the positive and negative effects that its implementation can bring to organizations. In this study, sentiment analysis of Twitter-based teleworking in a post-pandemic COVID-19 context was conducted. A set of Twitter conversations is examined by applying text mining and opinion analysis techniques. The results show the prevalence of positive sentiments regarding telework. In addition, opinions are generally associated with confidence, anticipation, and joy. According to the results, it is recommended to consider telework as an opportunity to improve worker well-being. However, it is important to consider some factors, such as the sector to which the company belongs, the characteristics of the job, and the working conditions.
Keywords: Sentiment analysis; Teleworking; Twitter; https://purl.org/pe-repo/ocde/ford#2.02.00